Environmentally driven immune imprinting protects against allergy - S. Erickson; B. Lauring; J. Cullen; R. Medzhitov (Nature, 2026)
Abstract Allergic diseases are caused by overexuberant type II immune responses mounted against environmental antigens 1 . The allergic state is typified by the presence of allergen-reactive immunoglobulin E (IgE), which triggers mast cell degranulation upon allergen encounter, manifesting in pruritis, oedema and, in severe cases, anaphylaxis. Over the past century, the prevalence of allergic diseases has increased markedly, suggesting that environmental rather than genetic factors are mediating this change 2 . Although many hypotheses connecting environment to allergy exist 3–6 , the biological mechanisms that underpin environmentally mediated protection from allergy are unknown. Here we show, using a mouse model of allergic disease, that exposure to immunostimulatory environments generated cross-reactive adaptive immune memory, which tracked with obstructed type II immune responses upon allergen exposure. We found that engagement of cross-reactive adaptive immunity protected against future allergic sensitization and suppressed established allergic responses. Cross-reactivity in a tolerogenic context also prevented allergy, with the effect extending across antigenically complex exposures even at low protein sequence similarity. Our findings demonstrate a mechanistic relationship between environment and allergy, with general implications for adaptive immune function in natural settings.